UML Models of Research Process in Empirical Software Engineering - Rhmann, Wasiur (International Journal of Computer Sciences and Engineering, 2025)
In recent years, Empirical software engineering is gaining popularity among the software engineering and research community to improve the software quality. However lack of clear understanding about how to do empirical research in software engineering poses threats of unreliable research results. |So to clear understand the process of doing research in empirical software engineering, Unified Modeling Language (UML) models are used. Unified Modeling Language in software engineering is used for designing and analysis of the software systems.